2019
DOI: 10.1021/acs.jnatprod.8b00920
|View full text |Cite
|
Sign up to set email alerts
|

Phloroglucinols with Immunosuppressive Activities from the Fruits of Eucalyptus globulus

Abstract: Five new phloroglucinol derivatives, eucalyptins C−G (1−5), together with 13 known analogues (6−18) were isolated from the fruits of Eucalyptus globulus. The structures and absolute configurations of 1−5 were established by means of spectroscopic data analysis, computational calculation methods, and single-crystal X-ray diffraction. Compounds 1−18 were investigated for their immunosuppressive effects in vitro, and 1, 2, 6, and 7 displayed moderate inhibitory activities with IC 50 values of 11.8, 10.2, 18.2, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Plants of Eucalyptus genus (Myrtaceae) are a prolific resource of phloroglucinol derivatives, especially formylated phloroglucinol meroterpenoids (FPMs) [1][2][3][4]. These Eucalyptus secondary metabolites not only possess multifarious bioactive properties, including protein tyrosine phosphatase 1B inhibitory [2], immunosuppressive [3], antimicrobial [4,5], antiviral [6], anticancer [7][8][9], AChE inhibitory [10], and anti-leishmanial [11] effects, but also have attracted significant attention from the synthetic organic chemistry community [12][13][14][15][16][17][18]. Eucalyptus robusta, a tall arbor indigenous to Australia, is widely cultivated in south China.…”
Section: Introductionmentioning
confidence: 99%
“…Plants of Eucalyptus genus (Myrtaceae) are a prolific resource of phloroglucinol derivatives, especially formylated phloroglucinol meroterpenoids (FPMs) [1][2][3][4]. These Eucalyptus secondary metabolites not only possess multifarious bioactive properties, including protein tyrosine phosphatase 1B inhibitory [2], immunosuppressive [3], antimicrobial [4,5], antiviral [6], anticancer [7][8][9], AChE inhibitory [10], and anti-leishmanial [11] effects, but also have attracted significant attention from the synthetic organic chemistry community [12][13][14][15][16][17][18]. Eucalyptus robusta, a tall arbor indigenous to Australia, is widely cultivated in south China.…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary structure‐activity relationship (SAR) of the isolated compounds indicated that the presence of an isovaleryl group in phloroglucinols is necessary for having better activity. However, these compounds also exhibited cytotoxicity in normal cells and may cause liver and cardiovascular toxicity [42] . From the fruits of E. globulus , also eucalyptin A ( 26 ), possessing an unprecedented carbon framework of phloroglucinol‐coupled sesquiterpenoid was extracted.…”
Section: Chemistry and Biological Activities Of Phloroglucinolsmentioning
confidence: 99%
“…13 compounds were isolated from the fruits of E. globulus, named as 3β-acetoxyurs-11-en-28,13-olide (6), betulonic acid (7), betulinic acid (8), alphitolic acid (9), 2α,3β-dihydroxyurs-12-en-28-oic acid (10), ursolic acid (11), 11,12-dehydrousolic acid lactone (12), euscaphic acid (13), 3-oxo-ursolicacid (14), corosolic acid (15), 3β,13β-dihydroxy-urs-11-en-28-oic acid-13lactone (16), Ilelatifol D (17), colosolic acid (18). [2,[7][8] Above-mentioned compounds 14 and 18 were isolated from the fruits of E. globulus for the first time.…”
Section: Triterpenoidsmentioning
confidence: 99%
“…[23] Qin et al [14 ] obtain ed ten new formyl-phloroglucinol-terpene meroterpenoids, named eucalypglobulusals A-J (49-58). Pham et al [15] obtained five new phloroglucinol derivatives, named as eucalyptins E-G (59-61), and thirteen known compounds were also isolated from the fruits of E. globulus, named as eucalyptin B (62), macrocarpal A (63), macrocarpal B (64), macrocarpal C (65), macrocarpal D (66), macrocarpal E (67), macrocarpal Q (68), eucarobustol E (69), eug lob al-V (70), eug lob al-III (71), 1-(2,6-dihydroxy-4methoxy-3,5-dimethylphenyl)-2-methylbutan-1-one (72), 1-(2,4dihydroxy-6-methoxy-3,5-dimethylphenyl)-3-meth-ylbutan-1one (73), cypellocarpa C (74). Seven phloroglucinol derivatives were accessed from the leaves of E. globulus, named as eucalyptone (75), macrocarpal H (76), macrocarpal I (77), macrocarpal J (78), euglobal-IVb (79), euglobal-VII (80), euglobal-IX (81).…”
Section: Phloroglucinol Derivativesmentioning
confidence: 99%
See 1 more Smart Citation